Allogeneic Hematopoietic Cell Transplant for Systemic Juvenile Idiopathic Arthritis and Macrophage Activation Syndrome. (24th May 2021) - Davidson, Nicole; Rangarajan, Hemalatha G.; Driest, Kyla; Bajwa, Rajinder P. S.; Polishchuk, Veronika; Abu-Arja, Rolla F.
Abstract : Systemic juvenile idiopathic arthritis (sJIA) is characterized by arthritis, fever, rash, lymphadenopathy, hepatosplenomegaly, and serositis. Macrophage activation syndrome is the most feared complication of sJIA with a high risk of mortality. We report a 16-year-old female diagnosed with refractory systemic juvenile idiopathic arthritis (sJIA) complicated by recurrent macrophage activation syndrome (MAS), severe joint disease, and lung involvement requiring prolonged immunosuppressive therapy. She received a matched unrelated allogeneic hematopoietic cell transplant (Allo-HCT) using a reduced-intensity conditioning regimen and is now, 3 years after the transplant, with complete resolution of sJIA symptoms, off immunosuppressants, and with significant improvement in the quality of life.